Características de las antiguas sociedades célticas de Irlanda y su posible utilización para un mejor conocimiento de los pueblos celtas de la Península Ibérica - Alberro, Manuel (Gerión. Revista de Historia Antigua, 2003)
Our present knowledge about the ancient Celtic societies of the Iberian peninsula derives from historical archaeological and linguistic evidence. On the other hand, the Celts of Ireland and Wales left behind a rich oral literature full of myths, legends and sagas that have been preserved. The analysis of the cultural traits of the insular Celtic societies presented in this paper could perhaps contribute to a better understanding of the ancient Celtic peoples of the Iberian peninsula.